2013
DOI: 10.1111/1742-6723.12081
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of chest pain patients discharged from the emergency department for early outpatient treadmill exercise stress testing

Abstract: Outpatient treadmill EST an average of 10 days post-discharge from emergency with chest pain did not result in adverse events despite reasonably high positive stress test rates. Consensus-based recommendations for inpatient testing or outpatient testing within 72 h of discharge should be reviewed in light of these data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In a smaller study in a similar population, Milano et al had similar findings, with 42% of patients returning for testing, but only 6% within 72 h [4]. Studies of patients with insurance, or in other countries, have had more success [5][6][7]. The yield of stress testing in our low risk population was low, but in line with other studies, which have shown that the incidence of coronary disease in low risk patients presenting to the ED is typically 1.5-2.5% [8,9].…”
mentioning
confidence: 71%
“…In a smaller study in a similar population, Milano et al had similar findings, with 42% of patients returning for testing, but only 6% within 72 h [4]. Studies of patients with insurance, or in other countries, have had more success [5][6][7]. The yield of stress testing in our low risk population was low, but in line with other studies, which have shown that the incidence of coronary disease in low risk patients presenting to the ED is typically 1.5-2.5% [8,9].…”
mentioning
confidence: 71%
“…and procedures. Since the guidelines were published a small body of evidence has challenged the need for routine testing showing adverse event rate <1% and low rates of identification of clinically relevant CAD [6][7][8]. Some authors have suggested clinical characteristics for the identification of very low risk groups including age and absence of known CAD [9,10].…”
Section: Resultsmentioning
confidence: 99%
“…In the Australian context Paoloni et al [8] retrospectively studied patients referred from ED for exercise stress testing.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, referral of patients to outpatient chest pain clinics may prove to be efficient and cost effective with studies finding that physician judgment alone results in 50% of patients not undergoing EST [18]. Outpatient stress testing up to 14 days after discharge from ED has been found to have no adverse patient outcomes, even in patients who were ultimately found to have major CAD [19].…”
Section: Discussionmentioning
confidence: 99%